Poétique de l’arbre et de la forêt. Une lecture bachelardienne de l’œuvre de Jean Giono (Altre Modernità, 2012)
By offering a reading and a perspective of Jean Giono's novel «L’homme qui plantait des arbres» (The Man Who Planted Trees), published in 1953, the following article would show what contributions Gaston Bachelard's philosophy might make to environmental imagination. As Jean Giono writes  “je crois qu’il est grand temps qu’on fasse une ‘politique de l’arbre’ bien que le mot politique semble bien mal adapté ”, we could say that it is time that this politic finds her poetic. The tree, as a primary image that emphasizes an upward dynamic in L’Air et les songes, and the forest, which rise a poetic of space in Bachelard (friend and reader of Gaston Roupnel, the historian of the French countryside), are precious figures in order to develop a poetic of nature. For this, however, there would be two defies. On the one hand, if the choice made by Gaston Bachelard to retain the tetralogy of the ancient cosmology produces a shift in thinking about the rêverie du végétal, an inadequacy in the valuation of the mineral on the organic, it doesn’t preclude it in principle. The phénoménologie du vegetal (phenomenology of plants) led to wonder what is about its relative neglected in the thinking of G. Bachelard, and about what may have close didactic reference to the four elements. On the other hand, it will be necessary to show how this apparently absent phenomenology, but legitimate in the work of philosopher, exceeds the critical ironic praise of the tree and of the forest that sees, in the best case, the mark of a naive romantic Arcadia (cf. Le Walden de Thoreau), and in the worst, a form of new obscurantism exiting, in a “nouvel order écologique” (new ecological order), the potential mark of an éco-fascism. Under these conditions, a poetic that dialectizes the tree and the forest can prepare an ecology of foundation.